α-Zirconium(IV) Phosphate: Static Study of 225Ac Sorption in an Acidic Environment and Its Kinetic Sorption Study Using natEu as a Model System for 225Ac - Ondrák, Lukáš; Ondrák Fialová, Kateřina; Vlk, Martin; Štamberg, Karel; Bruchertseifer, Frank; Morgenstern, Alfred; Kozempel, Ján (Materials (Basel, Switzerland), 2023)
Zirconium phosphate (ZrP), especially its alpha allotropic modification, appears to be a very promising sorbent material for the sorption and separation of various radionuclides due to its properties such as an extremely high ion exchange capacity and good radiation stability. Actinium-225 and its daughter nuclide 213Bi are alpha emitting radioisotopes of high interest for application in targeted alpha therapy of cancer. Thus, the main aim of this paper is to study the sorption of 225Ac on the α-ZrP surface and its kinetics, while the kinetics of the sorption is studied using natEu as a non-radioactive homologue of 225Ac. The sorption properties of α-ZrP were tested in an acidic environment (hydrochloric and nitric acid) using batch sorption experiments and characterized using equilibrium weight distribution coefficients Dw (mL/g). The modeling of the experimental data shows that the kinetics of 225Ac sorption on the surface of α-ZrP can be described using a film diffusion model (FD). The equilibrium weight distribution coefficient Dw for 225Ac in both hydrochloric and nitric acid reached the highest values in the concentration range 5.0-7.5 mM (14,303 ± 153 and 65,272 ± 612 mL/g, respectively). Considering the results obtained in radioactive static sorption experiments with 225Ac and in non-radioactive kinetic experiments with natEu, α-ZrP seems to be a very promising material for further construction of a 225Ac/213Bi generator.
Keywords: bismuth-213; zirconium; actinium-225; phosphate; kinetics; sorption